2008
DOI: 10.1002/pen.20978
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic hydrogen bonding inpoly(styrene‐co‐acrylic acid)/poly(styrene‐co‐4‐N,N‐dimethylacrylamide) blends

Abstract: FTIR study of the hydrogen bonding interactions within blends of different ratios of poly(styrene-co-acrylic acid) containing 18, 27, and 32 mol% of acrylic acid (SAA) and poly(styrene-co-N,N-dimethylacrylamide) containing 17 mol% of N,N-dimethylacrylamide (SAD-17) was carried out qualitatively and quantitatively in the temperature range varying from room temperature to 2108C. Two new bands characterizing these interactions appeared in the 1800-1550 cm -1 region at 1730 cm -1 and 1616 cm -1 and are attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…The same study also confirmed that spacing the carboxylic groups within polystyrene matrix optimized the hydrogen bonding interactions in poly (styrene‐co‐acrylic acid)/poly (styrene‐co‐N, N‐dimethylacrylamide) homoblends 19…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The same study also confirmed that spacing the carboxylic groups within polystyrene matrix optimized the hydrogen bonding interactions in poly (styrene‐co‐acrylic acid)/poly (styrene‐co‐N, N‐dimethylacrylamide) homoblends 19…”
Section: Resultsmentioning
confidence: 52%
“…It is worth recalling that we previously showed19 that while SAA18/SAD17 formed homogeneous phase in butan‐2‐one, turbid solutions were observed in the same common solvent with SAA32/SAD17 systems. All these blends, as‐cast from butan‐2‐one, exhibited a single Tg.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It should be also noted that the hydrogen bonding between the two AAc units is also possible. Nevertheless, the dimethylamide group is well‐known as a strong hydrogen bonding acceptor, and as much more DMAAm units exist in the ion gel than AAc units, the hydrogen bonding between DMAAm and AAc groups would be dominant …”
Section: Characterization Results For Synthesized Polymersmentioning
confidence: 99%
“…In a previous article,13 we have used FTIR spectroscopy to study the hydrogen bonding interactions within homoblends of poly(styrene‐ co ‐acrylic acid) containing 18, 27, and 32 mol % of acrylic acid (SAA18, SAA27, and SAA32, respectively) and poly(styrene‐ co ‐ N,N ‐dimethylacrylamide) containing 17 mol% of N,N ‐dimethylacrylamide (SAD17). Equilibrium constants describing both self‐association K 2 and interassociation K A and the enthalpies of hydrogen bonding formation were experimentally determined using a curve fitting analysis of the FTIR spectra as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%